Konsekwencje wychowywania się w rodzinie z problemem alkoholowym - bagaż na całe życie - Włodarczyk, Ewa (My University, 2016)
The article is dedicated to the problems of children raised by one or both parents addicted to alcohol who experience a negative impact of that situation in the area of their psychosocial functioning (in the current phase of their lives, as well as in adulthood).
Keywords: rodziny z problemem alkoholowym; dzieci; zaburzenia w rozwoju